Worker Reciprocity and Employer Investment in Training - Edwin Leuven; Hessel Oosterbeek; Randolph Sloof; Chris van Klaveren (Tinbergen Institute, 2002)
Standard economic theory predicts that firms will not invest in general training and will underinvest in specific training. Empirical evidence, however, indicates that firms do invest in general training of their workers. Evidence from laboratory experiments points to less underinvestment in specific training than theory predicts. We propose a simple model in which a firm invests the socially optimal amounts in general and specific training if the worker is sufficiently motivated by reciprocity. A reciprocal worker may be willing to give the firm a full return on its investment. We present empirical evidence that supports the proposed mechanism. Workers with a high sensitivity to reciprocity have 15% higher training rates than workers with a low sensitivity to reciprocity.
Keywords: J41; 330; Training; Reciprocity; Betriebliches Bildungsmanagement; Leistungsmotivation; Theorie